Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Training effects of affordance judgments in four different settings: towards developing a training battery for affordance judgments - Milena S. Gölz; Isabel Bauer; Lisa Finkel; Cedric Rosati; Andrea Wenzel; Tobias Herrmann; Kenneth F. Valyear; Jennifer Randerath (Experimental Brain Research, 2025)
Training affordance judgments (AJs) across different settings, such as judging whether an object is within reach or an obstacle conquerable, could be meaningful to older adults and neurological patients with diminished judgment behaviors. The long-term aim is to develop a comprehensive training battery with different types of AJ tasks. The present study used a between-subjects design to evaluate trainability in four different settings. Judgment behavior of 52 healthy young adults was trained (80 trials) in one out of four settings (per trained task N = 13): 1. Reaching horizontally forward for an object, 2. Fitting one hand horizontally into an aperture, 3. Fitting upright under a horizontal barrier, and 4. Stepping over a hurdle. Participants’ judgment performance was assessed pre- versus post-training. Additionally, to assess whether other AJ-based tasks as potential distractors may override training effects, the other three non-trained tasks were presented, and subsequently, judgment performance in the trained task was assessed once more. Accuracy, judgment tendency, and perceptual sensitivity served as dependent variables. A Friedman Test revealed a main effect of time point in all three variables. Post hoc analyses showed significant improvements in the trained task even after exposure to other AJ tasks. The results suggest that in young healthy adults, AJs can be trained effectively within different AJ settings, and improvements within one setting can last, even when AJs in other settings are solved in between. Our study provides proof of principle and an important step towards developing a training battery for AJs.

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Diversified innovations in the health sciences: Proposal for a Diversity Minimal Item Set (DiMIS) - Gertraud Stadler; Marie Chesaniuk; Stephanie Haering; Julia Roseman; Vera Maren Straßburger; Schraudner Martina; Ahmad Aisha-Nusrat; Auma Maisha; Banas Kasia; Borde Theda; Buspavanich Pichit; Dewey Marc; et al. (Sustainable Chemistry and Pharmacy, 2023)

Evaluating the Safety of Intra-Articular Mitotherapy in the Equine Model: A Potential Novel Treatment for Osteoarthritis - Jennifer M. Cassano; Krzysztof Marycz; Marta Horna; Marcos Perez Nogues; Jessica M. Morgan; Daniel B. Herrmann; Larry D. Galuppo; Natalia Vapniarsky (Journal of Equine Veterinary Science, 2023)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Toxicokinetics and toxicodynamics of the fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine and furanoyl-1-benzyl-4-anilinopiperidine - Tanja M. Gampfer; Lea Wagmann; Yu Mi Park; Annelies Cannaert; Jennifer Herrmann; Svenja Fischmann; Folker Westphal; Rolf Müller; Christophe P. Stove; Markus R. Meyer (Archives of Toxicology, 2020)
The two fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine (4F-Cy-BAP) and furanoyl-1-benzyl-4-anilinopiperidine (Fu-BAP) have recently been seized as new psychoactive substances (NPS) on the drugs of abuse market. As their toxicokinetic and toxicodynamic characteristics are completely unknown, this study focused on elucidating their in vitro metabolic stability in pooled human liver S9 fraction (pHLS9), their qualitative in vitro (pHLS9), and in vivo (zebrafish larvae) metabolism, and their in vitro isozyme mapping using recombinant expressed isoenzymes. Their maximum-tolerated concentration (MTC) in zebrafish larvae was studied from 0.01 to 100 µM. Their µ-opioid receptor (MOR) activity was analyzed in engineered human embryonic kidney (HEK) 293 T cells. In total, seven phase I and one phase II metabolites of 4F-Cy-BAP and 15 phase I and four phase II metabolites of Fu-BAP were tentatively identified by means of liquid chromatography high-resolution tandem mass spectrometry, with the majority detected in zebrafish larvae. N -Dealkylation, N -deacylation, hydroxylation, and N -oxidation were the most abundant metabolic reactions and the corresponding metabolites are expected to be promising analytical targets for toxicological analysis. Isozyme mapping revealed the main involvement of CYP3A4 in the phase I metabolism of 4F-Cy-BAP and in terms of Fu-BAP additionally CYP2D6. Therefore, drug-drug interactions by CYP3A4 inhibition may cause elevated drug levels and unwanted adverse effects. MTC experiments revealed malformations and changes in the behavior of larvae after exposure to 100 µM Fu-BAP. Both substances were only able to produce a weak activation of MOR and although toxic effects based on MOR activation seem unlikely, activity at other receptors cannot be excluded.

An endothelial cell line infected by Kaposi’s sarcoma–associated herpes virus (KSHV) allows the investigation of Kaposi’s sarcoma and the validation of novel viral inhibitors in vitro and in vivo - Tatyana Dubich; Anna Lieske; Susann Santag; Guillaume Beauclair; Jessica Rückert; Jennifer Herrmann; Jan Gorges; Guntram Büsche; Uli Kazmaier; Hansjörg Hauser; Marc Stadler; Thomas F. Schulz; et al. (Journal of Molecular Medicine, 2019)

ForC: a global database of forest carbon stocks and fluxes - Kristina J. Anderson‐Teixeira; Maria M. H. Wang; Jennifer C. McGarvey; Valentine Herrmann; Alan J. Tepley; Ben Bond‐Lamberty; David S. LeBauer (Ecology, 2018)
Forests play an influential role in the global carbon (C) cycle, storing roughly half of terrestrial C and annually exchanging with the atmosphere more than five times the carbon dioxide ( CO 2 ) emitted by anthropogenic activities. Yet, scaling up from field‐based measurements of forest C stocks and fluxes to understand global scale C cycling and its climate sensitivity remains an important challenge. Tens of thousands of forest C measurements have been made, but these data have yet to be integrated into a single database that makes them accessible for integrated analyses. Here we present an open‐access global Forest Carbon database (ForC) containing previously published records of field‐based measurements of ecosystem‐level C stocks and annual fluxes, along with disturbance history and methodological information. ForC expands upon the previously published tropical portion of this database, TropForC ( https://doi.org/10.5061/dryad.t516f ), now including 17,367 records (previously 3,568) representing 2,731 plots (previously 845) in 826 geographically distinct areas. The database covers all forested biogeographic and climate zones, represents forest stands of all ages, and currently includes data collected between 1934 and 2015. We expect that ForC will prove useful for macroecological analyses of forest C cycling, for evaluation of model predictions or remote sensing products, for quantifying the contribution of forests to the global C cycle, and for supporting international efforts to inventory forest carbon and greenhouse gas exchange. A dynamic version of ForC is maintained at on GitHub ( https://GitHub.com/forc-db ) , and we encourage the research community to collaborate in updating, correcting, expanding, and utilizing this database. ForC is an open access database, and we encourage use of the data for scientific research and education purposes. Data may not be used for commercial purposes without written permission of the database PI . Any publications using ForC data should cite this publication and Anderson‐Teixeira et al. (2016a) (see Metadata S1 ). No other copyright or cost restrictions are associated with the use of this data set.

Schätze aus dem Boden: innovative Prozesse zur Wirkstofffindung - Stephan Hüttel; Jennifer Herrmann; Rolf Müller (BIOspektrum, 2013)

Activity-guided screening of bioactive natural compounds implementing a new glucocorticoid-receptor-translocation assay and detection of new anti-inflammatory steroids from bacteria - Katrin Kaufmann; Luke Simmons; Jennifer Herrmann; Gertrud Schwär; Nora Luniak; Rolf Müller (Biotechnology Letters, 2013)